Synergy - Latash, Mark L., 1953- (New York ; Oxford : Oxford University Press, 2008)
'Synergy' dicusses a general problem in biology - the lack of an adequate language for formulating biologically specific problems. It describes the recent progress in the control and coordination of human movement, beginning with a brief history of movement studies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human mechanics; Biomechanics